The role of heteropolysaccharides in developing oxidized cellulose nanofibrils. (25th June 2016) - Meng, Qijun; Fu, Shiyu; Lucia, Lucian A.
Highlights: The influence of hemicelluloses on process of TEMPO-mediated oxidation. The influence of hemicelluloses on TOCNs suspension's properties. The feature of TOCN from materials is different due to the presence of hemicellulose. Abstract: A fundamental study was undertaken to determine the general role of heteropolysaccharides during the production of TEMPO-oxidized cellulose nanofibrils (TOCNs). Four major fiber resources, viz., fully bleached kraft pulps of softwood and hardwood varieties (pine, eucalyptus) and non-woods (bamboo, bagasse) were used because of their substantial morphological differences and relative abundance. The effect of heteropolysaccharides during TEMPO-mediated oxidation and high-pressure homogenization for TOCNs production was investigated under constant conditions. Most galactoglucomannans were removed during oxidation, whereas the majority of xylans were retained. The galactoglucomannans, however, non-beneficially consumed NaClO, the terminal TEMPO oxidant, while xylans adversely affected carboxylate group formation by limiting chemical accessibility to cellulose. However, lower xylans content led to more transparent and processable suspensions, while during mechanical processing, heteropolysaccharides supported nanofibrillation. The average length of the final TOCNs from eucalyptus, bamboo, bagasse, and pine were 290, 350, 360 and 370 nm, respectively, with average widths of ∼4 nm.